1993
DOI: 10.1073/pnas.90.4.1551
|View full text |Cite
|
Sign up to set email alerts
|

Three unusual modifications, a D-arabinosyl, an N-methyl, and a carbamoyl group, are present on the Nod factors of Azorhizobium caulinodans strain ORS571.

Abstract: Azorhizobium caulians strain 0RS571 is a symbiont of the tropical legume Sesbania rosrat. Upon nod gene induction with naringenin, strain 0RS571 secretes into the culture medium Nod factors that morphologically change the host plant-in particular, deformed root hairs (Hai/Had) and meristematic foci are formed at the basis of lateral roots. The latter infrequently develop further into nodule-like structures. The azorhizobial Nod factors are chitin tetramers or pentamers, N-acylated at the nonreducing-end glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
90
1
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(92 citation statements)
references
References 23 publications
(21 reference statements)
0
90
1
1
Order By: Relevance
“…More shown that A. caulinodans ORS571, the strain used as an inoculant in this study, also produces lipooligosaccharidic Nod factors (21). In S. rostrata, these factors elicit the division of cortical cells at the axils of lateral roots (21) (16) and Lotus corniculatus (40). Infection droplets containing several bacteria have also been noted for Vigna radiata (25).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…More shown that A. caulinodans ORS571, the strain used as an inoculant in this study, also produces lipooligosaccharidic Nod factors (21). In S. rostrata, these factors elicit the division of cortical cells at the axils of lateral roots (21) (16) and Lotus corniculatus (40). Infection droplets containing several bacteria have also been noted for Vigna radiata (25).…”
Section: Discussionmentioning
confidence: 92%
“…During the last decade, different groups have shown that nodulating rhizobia produce lipooligosaccharidic Nod factors (18,32), which are able to induce inner cortical cell divisions (32,36) and nodule development in alfalfa (36). More shown that A. caulinodans ORS571, the strain used as an inoculant in this study, also produces lipooligosaccharidic Nod factors (21). In S. rostrata, these factors elicit the division of cortical cells at the axils of lateral roots (21) (16) and Lotus corniculatus (40).…”
Section: Discussionmentioning
confidence: 98%
“…The first deformation occurs within 1 h after Nod factor application, whereas an increased cytoplasmic streaming occurs within 30 min (data not shown). In most other studies, root hair deformation was first scored several days after Nod factor application (Lerouge et al, 1990;Spaink et al, 1991;Price et al, 1992;Sanjuan et al, 1992;Schultze et al, 1992;Mergaert et al, 1993). Therefore, it is not clear whether such studies provide an accurate comparison of the abilities of different Nod factors to induce deformation.…”
Section: Discussionmentioning
confidence: 99%
“…105, 1994 deformation was scored 3 h after inoculation with R. leguminosarum bv trifolii and these deformed root hairs were present in a zone located 2 to 5 mm from the tip (Bhuvaneswari and Solheim, 1985). However, in a11 but one (Firmin et al, 1993) of the studies to determine Nod factor activity, root hair deformation was examined severa1 days after addition of Nod factor (Lerouge et al, 1990;Spaink et al, 1991;Price et al, 1992;Sanjuan et al, 1992;Schultze et al, 1992;Mergaert et al, 1993).…”
Section: Research (Nwo)mentioning
confidence: 99%
“…NFs and related lipochitin oligosaccharides are known for their strong plant growth promoting effects (Dyachok et al, 2002;Souleimanov et al, 2002;Prithiviraj et al, 2003) and have been shown to cause root hair induction (Hai) on vetch (Vicia sativa subsp. nigra; Roche et al, 1991;Zaat et al, 1987Zaat et al, , 1989Tak et al, 2004), S. rostrata (Mergaert et al, 1993), and L. japonicus (van Spronsen et al, 2001). van Brussel et al (1992) observed the induction of cortical root hair formation upon application of mitogenic NFs in the absence of bacteria.…”
Section: Discussionmentioning
confidence: 99%